A laser-induced TiO2-decorated graphene photoelectrode for sensitive photoelectrochemical biosensing. Issue 34 (8th April 2019) - Ge, Lei; Hong, Qing; Li, Hui; Li, Feng
Abstract : Direct-laser-writing of TiO2 -decorated graphene on indium-tin oxide glass was demonstrated to fabricate a unique photoelectrode for sensitive photoelectrochemical biosensing. Abstract : Herein, direct-laser-writing of TiO2 -decorated graphene on indium-tin oxide glass was demonstrated to fabricate a unique photoelectrode with a rapid and stable photoelectrochemical response under visible light; this photoelectrode was then applied in a photoelectrochemical enzymatic biosensor for the sensitive detection of an acetylcholinesterase inhibitor.